Total Factor Productivity in Chilean Manufacturing Sector [la Productividad Total de Factores en el Sector Manufacturero Chileno] - Gonzalez-Cid, M (Universidad Externado de Colombia, 2016)
The present research analyzes the Total Factor Productivity (TFP) change in the Chilean manufacturing sector through the calculation of the Malmquist index for the period 1998 - 2010. The Data Envelopment Analysis (DEA), which allows the calculation of the Malmquist index as an estimator of the ptf change and the decomposition of productivity change into technological change and technical efficiency. The main results indicate that during the period, the ptf has diminished mainly because of the technological change while the technical efficiency remains constant. © 2016, Universidad Externado de Colombia. All rights reserved.